Clinical profile of unclassifiable interstitial lung disease: Comparison with chronic fibrosing idiopathic interstitial pneumonias. Issue 1 (January 2018) - Traila, Daniel; Oancea, Cristian; Tudorache, Emanuela; Mladinescu, Ovidiu Fira; Timar, Bogdan; Tudorache, Voicu
Objective: Unclassifiable interstitial lung disease (ILD) is a common problem in clinical practice. These patients pose a distinct challenge with regard to appropriate evaluation and management. We investigated the clinical features and prognosis of unclassifiable ILD and compared its clinical profile with that of idiopathic pulmonary fibrosis (IPF) and idiopathic nonspecific interstitial pneumonia (NSIP). Methods: Patients with IPF (n = 40), NSIP (n = 14), and unclassifiable ILD (n = 27) were selected from an ongoing database. Baseline clinical features, pulmonary function, and the extent of fibrosis on high-resolution computed tomography (HRCT) were evaluated. Mortality was estimated based on the ILD–Gender, Age, Physiology (ILD-GAP) index and composite physiologic index (CPI). Results: IPF was associated with the worst survival (hazard ratio [HR] = 4.361 compared with NSIP), followed by unclassifiable cases (HR = 1.251 compared with NSIP). Increasing mortality was significantly impacted by age (HR = 1.04 per 1-year increase), lower carbon monoxide diffusing capacity of the lung (HR = 0.97), HRCT interstitial score (HR = 1.119 per 1-point increase), ILD-GAP score (HR = 1.570 per 1-point increase), and CPI (HR = 1.039 per 1-point increase). Conclusions: Patients with unclassifiable ILD had an intermediate prognosis between that of IPF and NSIP. Patients at high risk of mortality can be identified using baseline clinical, physiological, and radiological features.